The impact of treatment modality and radiation technique on outcomes and toxicity of patients with locally advanced oropharyngeal cancer1. (12th February 2013) - Al‐Mamgani, Abrahim; van Rooij, Peter; Verduijn, Gerda M.; Mehilal, Robert; Kerrebijn, Jeroen D.; Levendag, Peter C.
Abstract Objectives/Hypothesis: To investigate the impact of treatment modality and radiation technique on oncologic outcomes and toxicity of patients with locally advanced oropharyngeal cancer (OPC). Study Design: Retrospective analysis of outcomes and toxicity. Methods: Between 2000 and 2011, 204 consecutive patients with locally advanced OPC were treated with definitive (chemo)radiotherapy using 3‐dimensional conformal (3DCRT) or intensity‐modulated radiotherapy (IMRT). Endpoints were local control (LC), regional control (RC), disease‐free survival (DFS), cause‐specific survival (CSS), and overall survival (OS), and toxicity. Results: After a median follow‐up of 44 months (range 4–134), the 5‐year Kaplan‐Meier estimates of LC, RC, DFS, CSS, and OS were 78%, 92%, 60%, 64%, and 48%, respectively. Grade 3 mucositis and dysphagia (feeding‐tube dependency) were reported in 75% and 65%, respectively. The overall incidence of grade ≥2 and grade 3 late toxicities were 44% and 16%, respectively. Dysphagia and xerostomia were the most frequently reported late toxicity. Chemotherapy was significantly predictive for improved outcomes and increased toxicity. IMRT was significantly correlated with reduced toxicity. Conclusions: Compared to radiation alone, chemoradiotherapy significantly improved oncologic outcomes, but with significantly increased toxicity. Compared to 3DCRT, the introduction of IMRT resulted in a significant reduction of acute and late toxicity with slightly better, or at least comparable, outcomes. Despite the improvements achieved by the implementation of chemo‐IMRT, different new strategies to further improve outcome and reduce toxicity need to be thoroughly investigated in prospective, preferably, randomized trials.